The effect of information on social preferences towards an outgroup of refugees: A field experiment - Leon Bajrami; David D. Loschelder; Mario Mechtel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Previous research has shown that individuals discriminate against outgroup members in economic decision-tasks (e.g., Chen and Li 2009, Hett et al. 2017, see also Social Identity Theory, Tajfel and Turner 1979). In this paper, we examine senders' economic decisions in a dictator game, given that the receiver belongs to a refugee outgroup. First, we find that providing stylized information about the perspective of the receiver influences senders' social preferences. Second, we show that political preferences matter substantially. Our data reveal that senders' political orientation moderates the effect of information on their social preferences: While the information treatment strengthens social preferences towards outgroup members for more left-wing oriented participants, the treatment effect on participants who favor more right-wing parties is even negative. Our experiment allows to derive policy implications on how attitudes towards refugees could be altered.
Keywords: 330; outgroup discrimination; social identity; social preferences; refugees; information; field experiment